An enhanced hybrid scheme to support IP-based smart object network - Wan Fariza Wan Abdul Rahman (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Smart object networks are potentially huge scale both in terms of the number of devices involved and the number of data generated by each device. IPv6 is the protocol of choice for smart object networks due to its features and readiness in providing an open and standard based technology for the endless number of applications. An IPv6 routing protocol for low-power and lossy networks (LLNs), known as RPL has been designed by Internet Engineering Task Force (IETF) for resource constrained smart objects. It is defined in RFC 6550 that RPL can support either Storing mode only or Non-Storing mode only. The main drawback of this idea is, a homogeneous Non-Storing mode RPL network will introduce a high level of communication overhead, and a homogeneous network of Storing mode RPL network will require too much memory resources. Frequent occurrence of loops in LLNs contributes to additional delay and memory consumption to buffer the packet. To address these problems, this thesis proposed an RPL enhancement scheme to support a hybrid mode RPL with consideration of loop-free repair. The implementation of loop-free local route repair in hybrid RPL can further reduce delay and memory constraint in handling loops while topology changes. In real-time applications such as smart health monitoring, the excessive delay is intolerable since it could affect the patient’s life. The evaluation techniques used in this thesis are simulation using Cooja Contiki simulator and mathematical analysis. The feasibility of the proposed RPL enhancement is verified experimentally by developing a few scenarios of non-hybrid RPL (pure Storing and pure Non-Storing) mode as well as hybrid mode RPL of various percentage of Storing and Non-Storing. The performance metrics measured are memory consumption (in term of routing entries), total end-to-end delay and total routing overhead. Based on the simulation results, the memory consumption reduction in hybrid network integrated with loop-free repair achieves 25.22% to 33.9% compared to the homogeneous ones. The proposed scheme contributes to a better performance in terms of packet delivery ratio (PDR) compared to homogeneous Storing and homogeneous Non-Storing network but with an increased delay cost. Significant decrement of the routing overhead cost compared to homogeneous Storing and homogeneous Non-Storing scheme without loop-free repair mechanism can also be seen. The impact is not so obvious in a small size network. However, as the network grows, an improvement of up to 33.9% is achieved. In addition to simulation approach, mathematical analysis has been considered to measure performance metrics such as memory consumption (in bytes), total end-to-end delay and route discovery routing overhead.